PREFORMULATION STUDIES OF PILOCARPINE HYDROCHLORIDE AS NIOSOMAL GELS FOR OCULAR DRUG DELIVERY - JAIN, NEELAM; VERMA, ANURAG (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Pilocarpine hydrochloride is a direct acting cholinergic parasympathomimetic agent which directly stimulates cholinergic receptor (M3). It is a drug used in the treatment of chronic open-angle glaucoma for over 100 years. Designing a new ophthalmic dosage form for pilocarpine hydrochloride compels performing preformulation studies for drug. Therefore, the current aim of the study was to investigate some of the important physicochemical properties of pilocarpine hydrochloride which can help to select subsequent approaches during the development of niosomal gel for ocular use. Methods: Preformulation studies of drug were carried out for identification (physical appearance, melting point, and UV spectrophotometric analysis), solubility profile, lipophilicity (partition coefficient), compatibility studies by Fourier-transform infrared (FTIR) spectroscopy, and thermal behavior by differential scanning calorimetry (DSC). Results: The melting point of pilocarpine hydrochloride was found to be 204 ± 3○C. The log P value was found to be 1.12 ± 0.02, from which it can be interpreted that drug is highly hydrophilic in nature. The scanned λmax was found to be 215 nm. No significant changes were found when FTIR spectra of physical mixture compared with FTIR spectra of pure drug and excipients. This indicates absence of any possible interaction between the drug and excipients which confirms the identity and purity of drug. DSC thermogram of pure drug showed a sharp exothermic peak at 191.923○C (area=68.890 mJ, delta H = 22.963 J/g), indicating the crystal melting point of the drug. Conclusion: These results suggest that the pilocarpine hydrochloride serves as suitable candidate for ocular drug delivery system.